Evaluation and Optimization of Adjacent Tunnel Light Environment Scheme to Low Carbon - Yingxia Yu; Haoyu Gu; Bin Liang; Qianyi Sun; Junjie Zou (Energy Science & Engineering)
ABSTRACT The distance between adjacent tunnels is relatively small, and the driver passes through the alternating light environment for a short time, which poses great safety hazards to driving. Guided by the low‐carbon concept, it is of great significance to find an optimized light environment solution that integrates safety, low‐carbon, and economy. Based on the adjacent tunnel between Shuigou River and Songjiawa, this article evaluates and optimizes traditional lighting schemes and sunshade schemes from the above three aspects. The results show that the overall uniformity of road surface luminance for both schemes is greater than 0.313, which meets the regulatory requirements and is a feasible solution. Compared to traditional lighting schemes, the sunshade scheme reduces carbon emissions by 37.23% throughout its lifecycle, and reduces the present value of its lifecycle costs by 19.51%. From a comprehensive evaluation of the life cycle, the sunshade scheme is superior to the traditional lighting scheme.